Action Research for Better Health in Cote d’Ivoire - World Bank (Washington, DC, 2012)
To base health sector reforms on issues identified by Ivoirien stakeholders and policy research carried out by them. In late 1994, a strategic management retreat of senior Ministry of Health officials initiated a process of issues identification. A World Bank project preparation facility advance in 1995 and a grant from the Government of Japan made it possible for action research to begin (action research refers to research that facilitates and is informed by implementation). By late 1995, the Ministry of Health had completed a full set of over thirty action research proposals. An International Development Association (IDA) credit equivalent to $40 million was approved in June 1996 to support the Cote d'Ivoire integrated health services development project.